Pharmacology of cannabinoids - Woranisarakul, Krittaya (Journal of Thai Stroke Society, 2021)
Cannabinoids is a substance which has an effect on cannabinoid receptors. There were three types of cannabinoids. Endocannabinoid is an endogenous cannabinoid in human body. Phytocannabinoid is an extraction from Cannabis. Synthetic cannabinoid is a synthetic product which are derived from phytocannabinoid. Cannabinoids bind to both cannabinoid receptor 1 (CB1) and cannabinoid receptor 2 (CB2) in a different binding affinity. The main effect of cannabinoid on CB1 is an inhibition of releasing neurotransmitters such as glutamate from pre-synaptic neuron. The biological effect of CB1 agonist has a potential therapeutic outcome in several pathological conditions, including chronic pain disorder and multiple sclerosis. Until present, Δ9-trans-tetrahydrocannabinol (Δ9-THC) and cannabidiol (CBD) are the most common phytocannabinoid that had been researching in clinical study.